The Moderation Role of E-Satisfaction And E-Trust on E-Loyalty of Travelin Application Users - Ardha Wulanigara; Euis Saribanon; Dian Artanti Arubusman (Dinasti Review, 2025)
In recent years, the tourism sector has undergone rapid digital transformation and growth. Angkasa Pura II launched the TRAVELIN application to cater to various needs of passengers at Angkasa Pura II airports. Through this application, passengers receive real-time flight reminders and access the locations of all shops, facilities, and ground transportation at the airport with a single touch. This study aims to examine the effect of E-Service Quality and E-Word of mouth on E-loyalty through E-satisfaction and E-trust.The research employs a quantitative method with a sample of 250 users of the Travelin application. Data were collected through questionnaires. The data were analyzed using SmartPLS 4 software. The study revealed that E-Service Quality significantly influences E-satisfaction, E-loyalty, and E-trust. Furthermore, E-Word of mouth significantly affects E-trust and E-loyalty. While E-satisfaction has a significant impact on E-loyalty, E-trust does not have a significant effect on E-loyalty. E-satisfaction is proven to be a significant mediating variable between E-Service Quality and E-loyalty among Travelin application users. On the other hand, E-trust is shown to be an insignificant mediating variable between E-Service Quality, E-loyalty, and E-Word of mouth, E-loyalty. The implication of this research highlights the need to enhance digital service quality (E-Service Quality) to improve customer satisfaction (E-satisfaction), which directly impacts user loyalty (E-loyalty).